Clinicopathological Features of Meningioangiomatosis Associated with Meningioma: A Case Report with Literature Review - Huajuan Cui; Huijuan Shi; Xiaodong Chen; Wei Wang; Riquan Lai; Anjia Han (Case Reports in Oncological Medicine)
Aim. To analyze the clinicopathological features of meningioangiomatosis (MA) associated with meningioma. Methods. We present one case of MA associated with meningioma. Histopathological examination and immunohistochemistry were used. Results. The age of the patient was 33-year-old man. Histopathologically, MA was characterized by vascular proliferation with perivascular meningothelial cells and/or fibroblast proliferation, entrapped glial islands. In addition, MA was associated with transitional meningioma. The patient was alive without evidence of recurrence at 18 months after mass resection. Conclusion. MA associated with meningioma is an extremely rare lesion. The differential diagnosis includes cortical invasion by meningioma and intracerebral schwannoma. Patients with MA associated with meningioma often have a good prognosis after operation.